Relative Neurotoxin Gene Expression in Clostridium botulinum Type B, Determined Using Quantitative Reverse Transcription-PCR - Lövenklev, Maria (American Society for Microbiology, 2004)
A quantitative reverse transcription-PCR (qRT-PCR) method was developed to monitor the relative expression of the type B botulinum neurotoxin (BoNT/B) gene (cntB) in Clostridium botulinum. The levels of cntB mRNA in five type B strains were accurately monitored by using primers specific for cntB and for the reference gene encoding the 16S rRNA. The patterns and relative expression of cntB were different in the different strains. Except for one of the strains investigated, an increase in cntB expression was observed when the bacteria entered the early stationary growth phase. In the proteolytic strain C. botulinum ATCC 7949, the level of cntB mRNA was four- to fivefold higher than the corresponding levels in the other strains. This was confirmed when we quantified the production of extracellular BoNT/B by an enzyme-linked immunosorbent assay and measured the toxicity of BoNT/B by a mouse bioassay. When the effect of exposure to air on cntB expression was investigated, no decline in the relative expression was observed in spite of an 83% reduction in the viable count based on the initial cell number. Instead, the level of cntB mRNA remained the same. When there was an increase in the sodium nitrite concentration, the bacteria needed a longer adjustment time in the medium before exponential growth occurred. In addition, there was a reduction in the expression of cntB compared to the expression of the 16S rRNA gene at higher sodium nitrite concentrations. This was most obvious in the late exponential growth phase, but at the highest sodium nitrite concentration investigated, 45 ppm, a one- to threefold decline in the cntB mRNA level was observed in all growth phases.